The Implementation af an Organizational Innovation: Examples of Mass Customizing Firms of the Capital Goods Industry - Kohl, Hendrik; Depner, Heiner (International Journal of Industrial Engineering and Management, 2010)
Mass customization can be viewed as an organizational innovation, because a realization of the strategy requests a restructuring of structures and processes in a firm. The implementation of an organizational innovation is a far more complex process compared to the one of a technological innovation. Thus, it is supposed that firms implementing an organizational innovation are heavily dependent on the acquisition of external knowledge. This paper analyses – based on German case studies – how firms of the capital goods industry proceed when introducing a mass customization strategy. At the centre of consideration are answers to the questions what kind of knowledge the firms need for the implementation, how much they depend on external knowledge and whether social, organizational or spatial proximity between the actors in the innovation process is relevant for the knowledge exchange. Article history: Received (22.06.2010); Revised (27.09.2010); Accepted (08.10.2010)